PENGEMBANGAN MODUL AJAR BAHASA INDONESIA BERBASIS ETNOLINGUISTIK PADA MATERI IDE POKOK SEBUAH PARAGRAF DI KELAS IV SEKOLAH DASAR - Isra Miranti Septia; Muhammadi; Elfia Sukma; Adrias (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the lack of contextual teaching materials in Indonesian language instruction, particularly regarding the main idea of a paragraph in fourth-grade elementary school, which causes students to struggle with understanding the content of reading passages. This study was conducted in fourth-grade classes at SD Negeri 03 Bandar Buat, SD Negeri 16 Pagambiran, and SD Negeri 35 Pagambiran. The objective of this study is to produce a valid, practical, and effective ethnolinguistics-based Indonesian language teaching module capable of improving students’ learning outcomes in identifying the main idea of a paragraph. The research design employed is a Research and Development (R&D) study using the 4D model, which includes the Define, Design, Develop, and Disseminate stages. The developed teaching module was validated by subject matter experts, media experts, and language experts using a validation sheet. The practicality test was conducted through teacher and student response questionnaires, while the effectiveness test was conducted through pre-tests and post-tests analyzed using N-Gain. The results of the study indicate that the teaching module achieved a validity level of 93.69%, categorized as highly valid, , practicality of 95.83% among teachers and approximately 97% among students in the “very practical” category, as well as effectiveness with an N -Gain at the pilot school, SD Negeri 03 Bandar Buat, was 89.52%, at the first implementation school, SD Negeri 16 Pagambiran, 93.45%, and at the second implementation school, SD Negeri 35 Pagambiran, 95.54%; all three schools fell into the effective category. Thus, the ethnolinguistics-based teaching module is deemed valid, practical, and effective for use in Indonesian language instruction.